Elementary Students' Perceptions of Creative Learning Through Food Chain Diorama Projects: A Case Study - Pratiwi, Laila Diah Ayu; Widiarti, Nuni (Journal of Innovation and Research in Primary Education, 2025)
This study investigates elementary students’ perceptions of the implementation of project-based learning through the Food Chain Diorama (DIONTANA) model in science education, with a focus on its contribution to creativity development. Employing a qualitative case study design, the research involved 30 fifth-grade students from SD Negeri 5 Metro Selatan who engaged in the DIONTANA project. Data were collected through observations, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that the DIONTANA project fostered student creativity across four Torrance dimensions—fluency, flexibility, originality, and elaboration—while enhancing conceptual understanding and collaborative skills. Three-dimensional dioramas served as cognitive bridges, transforming abstract ecological concepts into concrete representations. Students reported high levels of motivation and engagement, supported by autonomy, competence, and social interaction. However, challenges such as time constraints, limited material access, and individual learning differences emerged. The study suggests adaptive strategies including flexible timelines, resource banks, differentiated mentoring, and school-community partnerships. These findings highlight the pedagogical value of integrating contextual, collaborative, and creativity-centered approaches in elementary science curricula to promote 21st-century competencies.